The software paradox : the rise and fall of the commercial software market - O'Grady, Stephen (O'Reilly Media, 2015)
Software is more important than ever today and yet its commercial value is steadily declining. Microsoft, for instance, has seen its gross margins decrease for a decade, while startups and corporations alike are distributing free software that would have been worth millions a few years ago. Welcome to the software paradox. In this O'Reilly report, RedMonk's Stephen O'Grady explains why the real money no longer lies in software, and what it means for companies that depend on that revenue. You'll learn how this paradox came about and what your company can do in response. This book covers: Why it's growing more difficult to sell software on a standalone basis How software has come full circle, from enabler to product and back again The roles that open source, software-as-a-service, and subscriptions play How software developers have become the new kingmakers Why Microsoft, Apple, and Google epitomize this transition How the paradox has affected other tech giants, such as Oracle and Salesforce.com Strategies your software firm can explore, including alternative revenue models.